1992
DOI: 10.1111/j.1600-0714.1992.tb00095.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Epstein‐Barr virus and human papillomavirus in oral mucosa of HIV‐Infected patients

Abstract: Epstein-Barr virus (EBV) has been implicated in the genesis of oral hairy leukoplakia (OHL). Initially, OHL was also associated with human papillomavirus (HPV) as evidenced by staining with antiserum to papillomavirus common structural antigens and reports of two HPV-positive OHL as detected by in situ DNA hybridization. The aims of this study were to determine the prevalence of EBV and HPV DNA in OHL and normal oral mucosa and to explain the basis for the staining of OHL tissues with antibodies to papillomavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 34 publications
(39 reference statements)
0
18
0
Order By: Relevance
“…[75][76][77][78][79][80] In the population infected with HIV, hairy leukoplakia is seen with relative frequency, appearing either before or after an established diagnosis of AIDS. It represents an opportunistic EBV infection and presents as an asymptomatic white patch that may be flat, vertically corrugated, or papillate (hairy).…”
Section: Hairy Leukoplakia Clinical Characteristicsmentioning
confidence: 99%
“…[75][76][77][78][79][80] In the population infected with HIV, hairy leukoplakia is seen with relative frequency, appearing either before or after an established diagnosis of AIDS. It represents an opportunistic EBV infection and presents as an asymptomatic white patch that may be flat, vertically corrugated, or papillate (hairy).…”
Section: Hairy Leukoplakia Clinical Characteristicsmentioning
confidence: 99%
“…A review of seven studies indicated that group II and III lesions, a marker for HIV and disease progression, which includes viral lesions of the mouth, were definitely less common, and HPVassociated oral lesions were possibly associated with HIV infection, respectively (80). Even if HPV-induced oral lesions associated with HIV infection is less common, many studies suggest that the chances of HPV infection might increase in proportion to the immune suppression caused by HIV infection (81)(82)(83)(84)(85)(86)(87)(88). In a cervical infection study, the risk of HPV infection in HIV-positive females and males increased with lower CD4 levels and higher HIV viral load (85).…”
Section: Hpv Of the Oral Cavity In Immunosuppressed Patientsmentioning
confidence: 99%
“…However, the immunological effects of HAART could not provide sufficient protection against different kinds of HPV-induced lesions in some HIV-infected patients (75). The prevalence of HPV infection in the normal oral mucosa between HIV-positive and -negative females and males was not significantly different, but the spectrum of HPV genotypes in HIV-positive females and males could be wider than HIV-negative ones (81)(82)(83)(84). We also showed that prevalence in adults was similar among healthy individuals and HIV-positive females and males (Terai et al unpublished …”
Section: Hpv Of the Oral Cavity In Immunosuppressed Patientsmentioning
confidence: 99%
See 2 more Smart Citations